Evaluation of a Large Renal Mass Using 99mTc-MIBI SPECT/CT in a Patient With Chronic Kidney Disease. (March 2017) - Rowe, Steven P.; Gorin, Michael A.; Javadi, Mehrbod S.; Allaf, Mohamad E.
Abstract : Abstract: The differentiation of benign and indolent renal masses from aggressive tumor histologies cannot be reliably performed by CT or MRI. Additionally, renal mass biopsy risks complications and has a nondiagnostic rate of 10% to 20%. 99m Tc-MIBI SPECT/CT has been shown to allow for the accurate differentiation of benign renal oncocytomas and hybrid oncocytic/chormophobe tumors from other more aggressive renal tumor types. We present the case of an 84-year-old man with chronic kidney disease and an 11.2-cm renal mass. Results of his 99m Tc-MIBI SPECT/CT allowed avoidance of a radical nephrectomy.